Improving productivity, quality and biofortification in groundnut (Arachis hypogaea L.) through sulfur and zinc nutrition in alluvial soils of the semi-arid region of India. (11th November 2020) - Noman, Heba M.; Rana, D. S.; Choudhary, Anil K.; Dass, Anchal; Rajanna, G. A.; Pande, Pooja
Abstract: Sulfur (S) fertilization is essentially required for improving the crop productivity and oil content especially in legume oilseeds like groundnut ( Arachis hypogaea ) in south-Asian soils most of which are S-deficient. Apart from S, zinc (Zn) is also deficient in south-Asian soils. Thus, Zn-fertilization may prove as a cost-effective and sustainable approach to produce Zn-biofortified groundnut kernels to combat Zn-malnutrition besides enhanced oil, protein and kernel productivity. Hence, a field experiment was conducted on S- and Zn-fertilization in groundnut using 3 S-levels (0, 20, 40 kg/ha), 4-Zn levels (0, 2.5, 5, 7.5 kg/ha) and 2 Zn-biofertilizer levels (control and Zn-biofertilizer) in a split-plot design replicated thrice in a south-Asian semi-arid environment. Application of 40 kg S/ha significantly improved the pod and kernel yield, oil content and oil yield, protein content and protein yield in groundnut. Zn-application substantially improved the pod and kernel yield, oil yield and protein yield upto 5 kg Zn/ha; while further increase to 7.5 kg/ha considerably declined the pod and kernel yield, oil and protein yield. Application of 2.5, 5.0 and 7.5 kg Zn/ha led to 7.8, 17 and 26.4% increase in Zn-content in groundnut kernels over control; however, 5.0 kg Zn/ha proved superior for harnessing higher Zn uptake at different growth stages and in different plant parts at harvest. Zn-biofertilizer enhanced the pod yield by ∼5%. Interaction effects stressed upon supplementing 2.5 kg Zn/ha with Zn-biofertilizer in harnessing groundnut productivity equivalent to sole use of 5 kg Zn/ha. Application of 40 kg S/ha and 5 kg Zn/ha enhanced pod productivity by 31.6 and 21.2%, respectively over control. Overall, dual application of 40 kg S/ha and 5 kg Zn/ha may prove highly beneficial to enhance the pod and kernel productivity, quality with Zn-biofortified groundnut kernels besides improving human and animal health in S and Zn-deficient south-Asian alluvial soils.